2010
DOI: 10.3923/pjbs.2010.794.801
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Identification of Foodborne Pathogens Colonizing Rice Grains in South Asia

Abstract: The aim of this study was to identify the foodborne pathogens mainly, Aspergillus sp. colonizing rice grains using cultural and microscopic methods. Four differential media (Czapek Dox Agar (CZA), Czapek Yeast Agar (CYA), Malt Extract Agar (MEA) and Czapek yeast 20% sucrose agar (CYA20S)) were used for differentiation of five Aspergillus sp., colonizing rice grains comparing with standard cultures. We studied macroscopic (colony color and diameter, conidia color, exudates, sclerotia and colony texture) and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some papers report the identification and the incidence of Aspergillus spp. colonising rice grains in South Asia (Reddy et al, 2010a), Brazil (de Carvalho et al, 2010Guimarães et al, 2010) and Nigeria (Somorin and Bankole, 2010); the detection of different mycotoxigenic fungi, including Aspergillus spp., regarded also stored rice in Africa (Surekha et al, 2011). Among these reports, only in Brazil low levels of aflatoxin contamination were reported (de Carvalho et al, 2010) and different Indian rice cultivars have been studied for the accumulation of AFB 1 after in vitro inoculation with A. flavus (Reddy et al, 2010b).…”
Section: 21mentioning
confidence: 99%
“…Some papers report the identification and the incidence of Aspergillus spp. colonising rice grains in South Asia (Reddy et al, 2010a), Brazil (de Carvalho et al, 2010Guimarães et al, 2010) and Nigeria (Somorin and Bankole, 2010); the detection of different mycotoxigenic fungi, including Aspergillus spp., regarded also stored rice in Africa (Surekha et al, 2011). Among these reports, only in Brazil low levels of aflatoxin contamination were reported (de Carvalho et al, 2010) and different Indian rice cultivars have been studied for the accumulation of AFB 1 after in vitro inoculation with A. flavus (Reddy et al, 2010b).…”
Section: 21mentioning
confidence: 99%
“…Conidia diameter also shows slight variation in all the isolates. Variations in conidiophore length and conidia size of A. flavus and A. niger was also observed by Reddy et al (2010).…”
Section: Discussionmentioning
confidence: 77%
“…Despite originating from different districts, isolates showed similarities in their morphological and cultural characteristics. There was not much variation in colony color and pigmentation of A. flavus and A. niger isolates (Reddy et al, 2010;Gautam and Bhadauria, 2012, Odhiambo et al, 2013and Baquiao et al, 2013 (Kumar et al, 2014, Navya et al, 2014and Amrita and Richa, 2014 have also reported significant differences in growth rate of Aspergillus isolates.…”
Section: Discussionmentioning
confidence: 93%
“…The isolated fungi were firstly identified by the morphological observations according to the previous studies ( Reddy et al., 2010 ; Nagaraja et al., 2016 ; Tralamazza et al., 2018 ) and then were validated by PCR analysis ( Munitz et al., 2014 ). All fungal strains were inoculated on PDA and cultured for 7 days at 28 ± 2°C in the dark.…”
Section: Methodsmentioning
confidence: 99%